Comparison and analysis study of sha-3 finallists - Taha, Imad; Alahmad, Mohammad; Munther, Khansaa (2012)
The competition of the NIST contenders in SHA-3 increased between the candidates hash functions to choose the winner in the end of 2012. However, NIST has outlined different requirements to measure different hash functions criteria such as; security, structure, and performance. Therefore, this paper addresses a comparative study of round 2 finalist SHA-3 candidates in; design of structure, complexity of security, with performance and cost, to measure the robustness of the algorithms through the Fundamentals Security Measurement Factors of Hash Function (FSMFHF) of Secure Hash Algorithm (SHA). As a result, from this comprehensive comparison study between the finalist SHA-3 candidates such as; BLAKE, Grostl, JH, Keccak, and Skein, the Keccak, as well as JH are regarding the crucial competitors for the security future in the end of 2012, are suitable designs for lightweight hash function, andGrostl hash function is tight in security, tight in structure in trade-off (speed/memory) to implement in Virtex-7 2000T of FPGAs family hardware.